New trends in convenience stores - Costa, André Pinto da (2018)
In the last few decades, several innovations appeared that completely transformed the concept of convenience all around the world. In Portugal, a country where convenience stores and gas stations exist side by side, the propagation of electric cars can quickly change what convenience means for the Portuguese customers – it is expected that these places become unnecessary if they do not adapt to new trends. Several questions arise: How can one engage customers that will now spend around 10/15 minutes waiting for their cars to charge? How can these stores become true entertainment centres instead of being just “places to buy gas”? How can managers prevent that these stores become “obsoletes”? And how can new trends (such as hybrid stores, “retailtainment” and interactive screens) impact Portuguese customers and their decision on where to shop? To try and answer even more questions, this project was developed in a joint effort between the author, Marketing Future Cast Lab and Galp. With the main purpose of studying the influence of future trends on Portuguese convenience stores, an extensive literature review and benchmark analysis phase was started. The most relevant trends were then used as a basis to create new concepts and innovative ideas while posterior testing (both quantitative and qualitative) validated/excluded them. By combining the knowledge obtained from the literature review, the feedback from the stakeholders of the project and the insights from the chosen methodologies, it was possible to conclude that there exists a serious possibility of a breakthrough in this sector through a new, perception-changing positioning on what is a convenience store. The focus should be, namely, on New Assortments (e.g. food and vending machines), Store-in-Store concepts (e.g. fresh food stations), Partnerships with recognized brands and investment on Digital/Technology. In the final remarks, managers are advised to acknowledge the vital need of accepting and implementing these trends, never losing focus with the fact that the only constant is change.